PENGARUH KONSENTRAT CAMPURAN KOHAY DAN DEDAK TERFERMENTASI DOSIS RHIZOPUS OLIGOSPORUS TERHADAP KADAR PROTEIN KASAR, SERAT KASAR, DAN LEMAK KASAR - Muhammad Juraid Wattiheluw (Indonesian Journal of Applied Sciences, 2012)
Purpose of the study was to evaluate the effect of concentrated mixture of KOHAY and bran dose Rhizopus oligosporus inoculum on the concentration of crudes of protein, fiber, and fat crude protein content, crude fiber, and crude fat fermented product. Research was carried out by the experimental methods. The first study is based on Completely Randomized Design (CRD) 3x3 factorial. The first factor (C1) is the concentrate mixture of KOHAY and bran, namely: a combination is 90% KOHAY with 10% bran, (C2) 80% KOHAY with 20% bran, and (C3) 70% KOHAY with 30% bran. The second factor is the dosage inoculum R.oligosporus, namely: (D1) 0,5% inoculum R. oligosporus, (D2) 0,6% inoculum R.oligosporus, and (D3) 0,7% inoculum R.oligosporus. Variables research include crude protein content, crude fiber, and crude fat. The results of the research showed that the increased nutrient value than the original material. The first stage of research is the concentrate mixture of KOHAY 90% and 10% bran fermented by R.oligosporus inoculum 0,6% (C1D6) showed that increased 34,43% crude protein, crude fiber decreased 10,99%, and crude fat decreased 2,71%.